Cryoballoon versus open irrigated radiofrequency ablation in patients with paroxysmal atrial fibrillation: the prospective, randomized, controlled, noninferiority FreezeAF study - Luik, Armin; Radzewitz, Andrea; Kieser, Meinhard; Walter, Marlene; Bramlage, Peter; Hörmann, Patrick; Schmidt, Kerstin; Horn, Nicolas; Brinkmeier-Theofanopoulou, Maria; Kunzmann, Kevin; Riexinger, Tobias; Schymik, Gerhard; et al. (Circulation, 2015)
Background—There is a lack of data on the comparative efficacy and procedural safety of open irrigated radiofrequency (RF) and cryoballoon catheter (CB) ablation for pulmonary vein isolation in patients with paroxysmal atrial fibrillation.Methods and Results—In a prospective, noninferiority study, 315 patients were randomly assigned to RF (n=159) or CB (n=156) ablation. The primary end point was freedom from atrial arrhythmia with absence of persistent complications. Patients were largely comparable between groups with more vascular disease in the RF group (8.2% versus 2.6% for CB; P=0.028). The primary end point at 12 months was achieved by 70.7% with RF and 73.6% with CB (multiple procedure success), including 31 redo procedures in each group (19.5% of RF versus 19.9% of CB; P=0.933). For the intention-to-treat population, noninferiority of CB was revealed for the predefined inferiority margin (risk difference, 0.029; 95% confidence interval, −0.074 to 0.132; P<0.001). Rates at 6 months were 63.1% and 64.1% for the RF and CB groups (single procedure success), and noninferiority was confirmed (risk difference, 0.010; 95% confidence interval, −0.097 to 0.116; P=0.002). Periprocedural complications for the index procedure were more frequent in the CB group (5.0% RF, 12.2% CB; P=0.022) with a significant difference in phrenic nerve palsies (0% RF, 5.8% CB; P=0.002).Conclusion—This large, prospective, randomized, controlled study demonstrates noninferiority of CB ablation versus RF ablation for treating patients with paroxysmal atrial fibrillation.Clinical Trial Registration—URL: http://www.clinicaltrials.gov. Unique identifier: NCT00774566.